Dapagliflozin in heart failure with preserved and mildly reduced ejection fraction: rationale and design of the DELIVER trial. (9th June 2021) - Solomon, Scott D.; de Boer, Rudolf A.; DeMets, David; Hernandez, Adrian F.; Inzucchi, Silvio E.; Kosiborod, Mikhail N.; Lam, Carolyn S.P.; Martinez, Felipe; Shah, Sanjiv J.; Lindholm, Daniel; Wilderäng, Ulrica; Öhrn, Fredrik; et al.
Abstract: Aims: Sodium–glucose co‐transporter 2 (SGLT2) inhibitors, originally developed as glucose‐lowering agents, have been shown to reduce heart failure hospitalizations in patients with type 2 diabetes without established heart failure, and in patients with heart failure with and without diabetes. Their role in patients with heart failure with preserved and mildly reduced ejection fraction remains unknown. Methods: Dapagliflozin Evaluation to Improve the LIVEs of Patients With PReserved Ejection Fraction Heart Failure (DELIVER) is an international, multicentre, parallel group, event‐driven, randomized, double‐blind trial in patients with chronic heart failure and left ventricular ejection fraction (LVEF) >40%, comparing the effect of dapagliflozin 10 mg once daily, vs. placebo, in addition to standard of care. Patients with or without diabetes, with signs and symptoms of heart failure, a LVEF >40%, elevation in natriuretic peptides and evidence of structural heart disease are eligible. The primary endpoint is time‐to‐first cardiovascular death or worsening heart failure event (heart failure hospitalization or urgent heart failure visit), and will be assessed in dual primary analyses – the full population and in those with LVEF <60%. The study is event‐driven and will target 1117 primary events. A total of 6263 patients have been randomized. Conclusions: DELIVER will determine the efficacy and safety of the SGLT2 inhibitor dapagliflozin, added to conventional therapy, in patients with heart failure and preserved and mildly reduced ejection fraction.